Aspek Makna Mana yang Hilang? : Penerapan Linguistik Fungsional Sistemik (SFL) dalam Penilaian Terjemahan - Machali, Rochayah (Jurnal Penerjemahan, 2023)
Translation assessment is important for two reasons: For creating the dialectics between theory and practice and for purposes of setting criteria and standards in translation assessments, in particular when we compare an SL text and its different TL versions (Machali, 2009:153). There are various theoretical frameworks that can be used in this context, among which are the Skopos or the Functionalism theories. However, it is not easy to apply these into practice, particularly when we are faced with loss of meaning that cannot be judged as ‘mistranslation’. Some of the general phrases that some evaluators often use are ‘too literal’, ‘not natural’, etc. These criteria, in fact, only emphasize one aspect of meaning, the experiential (i.e., who does what to whom, why, when andhow). As such, assessors have ignored the fact that a text is a realization of three aspects of meaning: the experiential (which is a part of ideational meaning), interpersonal, and textual (Halliday, 1994; Mathiessen, 1992;Catford, 1965). In this framework of SFL, these three aspects of meaning must be considered together as ‘criteria’ for translation assessment. There are challenges and problems in this application of SFL, particularlywhen we are faced with such notions as ‘naturalness’ in translation or ‘translation as ideology’. Key words: Systemic Functional Linguistics (SFL), Exeperiential, interpersonal, textual, mistranslation, translation as ideology, criteria, assessment.